Novel Floating Adsorbent for Water Treatment: Organically Modified Layered Alkali Silicate by Facile Mechanochemical Reaction - Sruamsiri, Donhatai; Shimojima, Atsushi; Ogawa, Makoto (ACS applied materials & interfaces, 2023)
Adsorption serves as an effective way to collect (remove) contaminants from aqueous solution. In the present study, a novel floating adsorbent was designed through surface modification of a layered alkali silicate (octosilicate) using a silane coupling reagent (chlorodimethyl[3-(2,3,4,5,6-pentafluorophenyl)propyl]silane) to collect metal ions from water. By conducting the grafting by solvent-free mechanochemical reaction at room temperature, the external surface of octosilicate was modified to be hydrophobic while preserving the ion exchange capability in the interlayer space. Characterizations of XRD, IR, SEM, TGA, 29Si MAS NMR, and 19F MAS NMR confirmed the successful grafting at the external surface of octosilicate particles. The modified silicate demonstrated buoyancy at the air–water interface, facilitating the concentration of methylene blue, Ni2+, and Pb2+ from aqueous solutions. The adsorbed amounts of metal ions on the floating adsorbent were greater than those reported for the common nonfloating adsorbents (zeolites, clays, and clay minerals).